Publishing Student Graduation Projects Based on the Semantic Web Technologies - Trinh, Linh Thi Ngoc; Hoang, Hung Bao; Nguyen, Hue Thi Hoa; Vo, Dung Hoang Phuong (Transactions on Engineering and Computing Sciences, 2018)
Linked Open Data is already widely available in several industries, such as libraries, biomedicine and Linked government data, etc. for data sharing, promoting semantic web development and maintaining a global culture of information exchange. In this paper, we focus on developling a linked data-based application for the management and publication of student graduation projects at ViethanIT library. Students can refer to these resources for further developing future research directions. In addition, the published student graduation projects are useful to detect plagiarism in other researches (projects). Therefore, we first introduce an ontology defined classes and properties to describe student graduation projects in the Korea-Vietnam Friendship IT College. We then outline how to apply the ontology along with SPARQL queries and RDFa to publish the student graduation projects on a semantic website.